Roque Espinosa (2014). Desmemoria y olvido. La economía arrocera en la cuenca del Guayas - Arrazola, Íñigo (Revista Economía, 2019)
Reseña de "Desmemoria y olvido. La economía arrocera en la cuenca del Guayas"